TRANSFORMASI WARISAN BUDAYA MENJADI WISATA EDUKASI: INISIATIF DEMONSTRASI PEMBUATAN BOKOR DI DESA BRESELA - Budiadnyani, Ni Putu; R. Aprilyani Dewi, Putu Pande; Indraswari, I Gusti Agung Ayu Pramita; Kusuma, Putu Sri Arta Jaya (Gapenas Publisher, 2025)
The transformation of cultural heritage into educational tourism presents a unique opportunity to not only preserve time-honored traditions but also stimulate local economies. This endeavor, however, demands nuanced strategies that carefully balance the need for authenticity with the imperative of accessibility. The